Antagonistic activity of two Bacillus strains against Fusarium oxysporum f. sp. capsici (FOC-1) causing Fusarium wilt and growth promotion activity of chili plant - Iqbal, Owais; Syed, Rehana Naz; Rajput, Nasir Ahmed; Wang, Yi; Lodhi, Abdul Mubeen; Khan, Rizwan; Jibril, Sauban Musa; Atiq, Muhammad; Li, Chengyun (Frontiers in Microbiology, 2024)
Fusarium oxysporum f. sp. capsici poses a significant position in agriculture that has a negative impact on chili plant in term of growth, fruit quality, and yield. Biological control is one of the promising strategies to control this pathogen in crops. Chili is considered as one of the most important crops in the Hyderabad region that is affected by fusarium wilt disease. The pathogen was isolated from the infected samples in the region and was confirmed by morphological characteristics as well as by PCR with a band of 488bp. The bacterial strains were isolated from the rhizosphere soil of healthy plant and also confirmed by PCR with a band of 1542bp.The molecular characterization of the fungal and bacterial strain has shown 99.9% homology with the retrieved sequences of Fusarium oxysporum f. sp. capsici and Bacillus subtilis from NCBI. The one-month-old Ghotki chili plants were inoculated with 1x10 5 cfu spore.ml -1 suspension and confirm that the FOC-1 is responsible for chili fusarium wilt disease. Subsequently, among the 33 screening Bacillus strains, only eleven showed antagonistic activity against F. oxysporum. Out of these, only two strains (AM13 and AM21) have shown maximum antagonistic activity against the pathogen by reducing the infection as well as promoting growth parameters of chili plants under both in vivo and greenhouse conditions. The study suggested that biological control is the most promising control strategy for the management of Fusarium wilt of chili in the field.